2012
DOI: 10.1111/j.1755-5949.2012.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Depression and One‐Year Prognosis of Patients with Stroke in Mainland China

Abstract: In our study, depression occurred in >40% of patients within the first year after stroke. Persistent depression is the first independent determinant of prognosis during the first year after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 36 publications
0
47
1
Order By: Relevance
“…The time of examination of the relationship between depression and functional recovery may be one reason for the inconsistency. Persistent depression and recurrent depression were found to be the top 2 independent determinants of 1-year outcome after stroke in our previous study, with an OR (95% CI) of 7.615 (5.011–11.572), and 4.701 (2.721–8.122), respectively [4]. Here, we found that the risk of functional impairment (mRS≥2) at 1-year in patients with persistent or recurrent depression was approximately 5 times that of patients with transient depression or without mood disorder.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The time of examination of the relationship between depression and functional recovery may be one reason for the inconsistency. Persistent depression and recurrent depression were found to be the top 2 independent determinants of 1-year outcome after stroke in our previous study, with an OR (95% CI) of 7.615 (5.011–11.572), and 4.701 (2.721–8.122), respectively [4]. Here, we found that the risk of functional impairment (mRS≥2) at 1-year in patients with persistent or recurrent depression was approximately 5 times that of patients with transient depression or without mood disorder.…”
Section: Discussionmentioning
confidence: 79%
“…Among the different time courses of PSD, persistent depression and recurrent depression had higher predictive values than transient depression [4].…”
Section: Introductionmentioning
confidence: 86%
“…: ISRCTN62169508). The details of the PRIOD study have been described elsewhere [10]. Briefly, this large-scale, multi-center study covering 56 hospitals nationwide was conducted between April 2008 and April 2010 to investigate the prevalence of PSD at different time points within the first year after stroke, and the association between PSD and stroke outcomes in stroke survivors in mainland China.…”
Section: Methodsmentioning
confidence: 99%
“…This 5-year follow-up study of stroke patients is a national project entitled the “Prospective Cohort Study on the Incidence and Outcome of Patients with Post-stroke Depression in China (PRIOD)” [10]. At baseline, patients in 56 hospitals nationwide were consecutively recruited and enrolled if they were aged 18 years or older, had an acute stroke according to WHO criteria [11] confirmed by CT or MRI within 14 days, could complete a clinical interview and provide informed consent.…”
Section: Methodsmentioning
confidence: 99%